2002
DOI: 10.1021/la025867k
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of α-Chymotrypsin and Lysozyme Entrapped in Water-in-Silicone Oil Emulsions

Abstract: A system of entrapping proteinaceous material in water-in-silicone oil emulsions using silicone surfactants is described. Although contact between cyclic and linear silicones and proteins is well-known to facilitate protein/enzyme denaturation, the additional presence of silicones bearing a few hydrophilic groups (silicone surfactants) in these W/O systems dramatically lowers the degree of protein denaturation. Spectrophotometric activity assays of R-chymotrypsin and lysozyme performed using a UV/visible spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 62 publications
(80 reference statements)
1
54
0
Order By: Relevance
“…That is why amphiphilic polymers are often used as emulsifying agents. A silicone oil necessitates a silicophilic/hydrophilic polymer, such as Abil EM-90 (Cetyl PEG/PPG-10/1 Dimethicone), 29,30 whereas a fluorinated continuous phase requires a fluorophilic/hydrophilic molecule, such as a PFPE-PEG block copolymer (perfluoropolyetherpolyethylene glycol). 31 Regarding biocompatibility, a non-hydrosoluble emulsifying agent is also most suitable to prevent contact of the cells with surfactants.…”
Section: Emulsion Formulationmentioning
confidence: 99%
“…That is why amphiphilic polymers are often used as emulsifying agents. A silicone oil necessitates a silicophilic/hydrophilic polymer, such as Abil EM-90 (Cetyl PEG/PPG-10/1 Dimethicone), 29,30 whereas a fluorinated continuous phase requires a fluorophilic/hydrophilic molecule, such as a PFPE-PEG block copolymer (perfluoropolyetherpolyethylene glycol). 31 Regarding biocompatibility, a non-hydrosoluble emulsifying agent is also most suitable to prevent contact of the cells with surfactants.…”
Section: Emulsion Formulationmentioning
confidence: 99%
“…The general observation is that the proteins are protected by silicones possessing an optimum balance of a hydrophilic/lipophilic environment [16]. Furthermore, in aspartic proteases, 17 invariant water molecules were found to maintain the structural stability of the enzyme in its native conformation [27].…”
Section: The Activity Of Free and Immobilized Pepsin In Organic Solventsmentioning
confidence: 99%
“…Furthermore the bound fibrinogen was found to be coagulable, as indicated by the thrombin dependent agglutination of the protein coated PDMS droplets [15]. For water-in-oil emulsions, Zelisko and Brook [16] have demonstrated that the presence of silicones bearing hydrophilic groups (silicone surfactants) leads to α-chymotrypsin and lysozyme being stable against denaturation.…”
mentioning
confidence: 99%
“…To better understand the role that silicone structure, particularly molecular weight, may have on protein denaturation we have undertaken a study of human serum albumin (HSA) denaturation and aggregation as a function of agitation intensity, silicone type (cyclic vs. linear, hydrophobic vs. surface active), protein concentration and, in particular, the molecular weights and molecular weight distributions of the silicone oils. HSA is a particularly convenient protein to study, as we and others have shown, because of the changes in fluorescence maxima that accompany denaturation [13,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 96%